Aktivitas Fisik Pada Pasien Beresiko Terjadinya Stroke di UPTD Puskesmas Gurah Kecamatan Gurah Kabupaten Kediri - Purnamasari , Vela; Lestari, Nove (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Introduction: Stroke is a disease that disrupts brain function, which if not treated and controlled properly can increase the risk of further complications and even death. Unhealthy lifestyle habits will trigger an increase in blood pressure, blood glucose, hypercholesterolemia so that it can increase the probability of stroke risk. This condition requires pharmacological and non-pharmacological management. Non-pharmacological management by modifying lifestyle, one of which is doing physical activity. The aim is to describe physical activity in patients at risk of stroke at UPTD Puskesmas Gurah, Gurah District, Kediri Regency. Method: Descriptive research design, population of 147 people and research sample of 34 people using purposive sampling technique according to research criteria. The study was conducted in September 2024 using physical activity variables in patients at risk of stroke. The research instrument used the Barthel Index questionnaire, data was measured and analyzed using a percentage formula and interpreted quantitatively. Results: The results of the study obtained 34 respondents which showed that most respondents had independent physical activity, namely 19 respondents (56%), almost half of the respondents had a mild level of dependence, namely 8 respondents (24%) and a small number of respondents had physical activity with moderate dependence, namely 7 respondents (20%). Physical activity in patients at risk of stroke is influenced by marital status, smoking habits, age, living with a nuclear family, previous medical history, physical activity habits, and uncontrolled stroke triggers. Conclusion: Through this study, it is expected that patients and families can also implement non-pharmacological management by controlling trigger factors, patient compliance in controlling stroke trigger factors regularly by managing stress, and doing physical activity regularly.